Peningkatan Hasil Belajar Matematika Siswa Pada Materi Geometri Menggunakan Pendekatan CTL Di Sekolah Dasar - Anggrayani, Riri; Zuryanty, Zuryanty (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
This study aims to describe the improvement of students' mathematics learningoutcomes in geometry using the CTL (Contextual Teaching Learning) approach in class IV SDN 15 Ampang Gadang in the 2018/2019 school year. This type of research is classroom action research with qualitative and quantitative approaches.The subjects of the study were the teacher and 21 students of grade IV SDN 15 Ampang Gadang. The study was conducted in two cycles, cycle I two meetings and cycle II one meeting. This is evidenced by the results of cycle 1 research aspects of planning cycle I 79% (B) increased in cycle II to 94% (AB) an increase of 15%, aspects of the implementation of the first cycle teacher 82% (B)increased in cycle II to 96% ( AB) an increase of 14%, aspects of the action of students of the first cycle 82(B) increased in cycle II to 96% an increase of 14%, and learning outcomes of cycle I with an average of 73 (C) and cycle II increased to 88 (AB) an increase of 15.